2001
DOI: 10.1021/ol016184j
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Rearrangement of Oxaziridines and Nitrones in the Hexahydroindole Series: A Convenient Synthetic Route to 1-Azabicyclo[5.2.0]nonan-2-ones as Novel RGD Mimetics

Abstract: [reaction: see text] Photolysis of oxaziridines a or nitrones b provides a convenient synthetic route to fused bicyclic lactams c adequately substituted on both cycles A and B as scaffolds for mimicking conformationally constrained beta-turn peptides as in the tripeptide RGD signaling motif of fibronectin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…It is noteworthy that gelselenidine (1) is the first example of gelsedine-type alkaloid bearing a 2,3-epoxybutane residue, which represents a rare class of Gelsemium alkaloids with an additional C 2 unit. 10 The molecular formula of 2 was established as C 19 13 C NMR and DEPT spectra of 2 displayed 19 signals, including two methyls, four methylenes, eight methines, one carbonyl, and four quaternary carbons, suggesting the presence of a monoterpenoid indole alkaloid. Comparison of the NMR data of 2 with those of gelsedine 6 revealed that their chemical shifts were similar, except for the absence of signals for H-20 and the presence of an oxygenated quaternary carbon signal at d C 93.4 ppm, indicating an oxygen atom was attached to C-20.…”
Section: Structural Elucidation Of Alkaloids 1e7mentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that gelselenidine (1) is the first example of gelsedine-type alkaloid bearing a 2,3-epoxybutane residue, which represents a rare class of Gelsemium alkaloids with an additional C 2 unit. 10 The molecular formula of 2 was established as C 19 13 C NMR and DEPT spectra of 2 displayed 19 signals, including two methyls, four methylenes, eight methines, one carbonyl, and four quaternary carbons, suggesting the presence of a monoterpenoid indole alkaloid. Comparison of the NMR data of 2 with those of gelsedine 6 revealed that their chemical shifts were similar, except for the absence of signals for H-20 and the presence of an oxygenated quaternary carbon signal at d C 93.4 ppm, indicating an oxygen atom was attached to C-20.…”
Section: Structural Elucidation Of Alkaloids 1e7mentioning
confidence: 99%
“…9 Addition with acetaldehyde 10 and subsequent oxidation of the olefinic bond would afford gelselenidine (1). On the other hand, after oxidation of the imine N 4 /C-20 19 of 8, gelseziridine (2) could be yielded. Compound 2 might be a biogenetic precursor of 18,19-nor-gelsedinetype alkaloids, such as gelsedilam, 15 which is characterized by the oxaziridine cleavage and b-scission.…”
Section: Possible Biogenetic Pathway For Alkaloids 1e4mentioning
confidence: 99%
“…The photolysis of nitrones afforded bicyclic lactams as an instance to demonstrate the synthetic utility of photochemical rearrangement (Scheme 35) [78,140].…”
Section: Synthesis Of Three-membered On-heterocyclesmentioning
confidence: 99%
“…The construction of seven-membered fused rings has been an important issue in the synthesis of natural products and the development of new medicines 1 . Generally, these bicyclic compounds can be constructed through ring closure of monocyclic compounds 2 3 , rearrangement reactions 4 5 6 7 , intramolecular cycloaddition of five-carbon synthons bearing a tethered alkyne 8 9 10 11 12 or modification of previously formed seven-membered rings 13 . However, these methods typically require complicated reactants with subtly positioned functional groups, a substantial amount of organic solvents, and a lengthy course or several synthesis and separation steps.…”
mentioning
confidence: 99%